Holocaust memory in the digital age : survivors' stories and new media practices - Shandler, Jeffrey (Stanford studies in Jewish history and culture., 2017)
Holocaust Memory in the Digital Age examines the nexus of new media and memory practices through an in-depth study of the Shoah Visual History Archive, the world's largest and most widely available collection of video interviews with Holocaust survivors, to understand how advances in digital technologies impact the practice of Holocaust remembrance.